A tale of two tails: asymmetry in Great Grey Shrike (Lanius excubitor) - Reuven Yosef; Anna Maria Kubicka; Martin Brandsma; Piotr Tryjanowski (Avian Research, 2018)
Abstract Background Asymmetry in the wild is a controversial, and to date, unresolved subject. Fluctuating asymmetry (FA) is the developmental instability (intra-individual variation) while, directional asymmetry (DA) expresses the asymmetry of the population mean. Methods We analysed 63 Great Grey Shrike (Lanius excubitor) skins at the Naturalis Biodiversity Center, Leiden, the Netherlands. The black markings on the tails were digitized in order to evaluate the symmetry of the two sides of each shrike. Ptilochronology helped understand if nutritional condition affected symmetry. Results ANOVA revealed no significant differences in size of the tail between sexes (F = 1.67, p > 0.05). However, there was significant difference in the shape of the black area in feathers between the sexes (F = 2.14, p < 0.05), and males had more elongated and slender black areas. Further, DA was observed only in males, but FA was noted in both sexes. Spearman correlation showed no significant association between FA score and tail features in both the sexes. However, in females, we observed a negative significant correlation between the number of fault and growth bars. The shape of the black area in the tail displayed no statistically significant association with the tail features in both sexes although growth bars influenced tail shape more than the number of fault bars. Conclusions We concluded that the characteristics discovered by us need to also be checked in the field and if they can be used to sex individuals. Also, chromatic manipulative studies are require to verify if DA influences sexual selection in the Great Grey Shrike.